Desain UI/UX Prototype SPP Metode Human Centered Design - Wahyu Muslimin; Eva Zuraidah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Al-Muttaqin Islamic Junior High School is a junior high school that still uses the Education Development Contribution (SPP) payment system by recording and recapitulating on SPP cards and payment books, but such a system is prone to damage and loss, causing data insecurity, besides that it also makes the payment process relatively long. The design of the user interface or user experience can influence users because of its attractive appearance and is expected to provide solutions to make it easier for officers in SPP payment services and to be able to make payment transactions that can be made. The target audience in this design is aimed at school treasurers and student guardians. The purpose of this study is to find out the stages of the tuition payment system process at Al-Muttaqin Islamic Middle School and then design a solution to the problem. In this study, the UI/UX SPP design was carried out at Al-Muttaqin Islamic Middle School by applying the stages of the Human Centered Design (HCD) method, namely understanding and specifying the context of use, specifying user needs, creating solution designs, and evaluating solution designs by conducting usability testing of designs. The results of the usability effectiveness test got a score of 90%, on learnability got a score of 92%, and on the satisfaction test (SUS) got a score of 87.8%, from the results of the test data it was declared successful. The process of recording and paying SPP will be faster, will reduce recording errors, record repetition, lost data, and make recording results more accurate